HEDONIC-MOTIVATION SYSTEM: PENGUKURAN INTENSI MAHASISWA DALAM PENGGUNAAN LEARNING MANAGEMENT SYSTEM - Suryo Widiantoro; Marfuah Marfuah (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2019)
One part of the academic information system at Universal University is a learning management system (LMS) that is used to support learning activities, so this system must be designed to be able to provide convenience for students as the main users. There are intrinsic motivational behaviors that need to be identified as consideration of factors that might have an impact on students' perceptions in their intentions to use a system. The Hedonic-motivation system (HMS) theory emphasized that in order to increase one's intention to use information systems, then the pleasure factor needs to be included along with the usability factor and the ease of use factor. The four HMS variables used in the measurement are ease of use, usability, enjoyment, and intention to use. The measurement results will be obtained dominant influential factors that can be used as a basic guideline in designing system interactions in the form of conceptual designs for the development of LMS at Universal University.